(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The traumatic epidemic is gaining momentum, including in Kyrgyzstan, most of whose territory is located at an altitude of more than 2000 m above sea level. At the same time, the microcirculatory bed in craniocerebral injuries is one of the most vulnerable areas of the angioarchitectonics of the brain, damage to which leads to the immediate activation of mechanisms for maintaining the constancy of perfusion and oxygenation of brain tissue. The purpose of to present the features of the remodeling of the microcirculation system of the brain in craniocerebral trauma in the highlands. Traumatic brain injury in the highlands causes the expansion of all links of the macrocirculatory bed with the phenomena of subarachnoid hemorrhages, edema and vacuolization of the wall. At the level of the microcirculatory bed – spasm of arterioles in combination with venous fullness. Craniocerebral trauma causes pronounced remodeling of macro- and micro-systems of the bloodstream of the brain, regardless of the location of the experiments, but to varying degrees. In high-altitude conditions, changes in the stromal component of vascular plexuses and desolation of arterioles with the phenomena of venous fullness are more pronounced than in low-altitude.